Anacardium occidentale Linn. Leaves and its medicinal properties - Wan Abdul Rashid, Puteri Nur Farahin; Haron, Normah; Darnis, Deny Susanti; Md Zin, Noor Hasniza (Malaysian Society for Biochemistry and Molecular Biology, 2022)
nacardium occidentale leaves, known as cashew leaves or Pucuk Gajus in Malay, is a member of the Anacardiaceae family that is widely grown in tropical countries such as Malaysia, India and Brazil. It had been traditionally used for treating many health problems as it contained many beneficial phytochemical compositions such as polyphenols, flavonoids, tannin, vitamin C and carotenoids. Its extract possesses antidiabetic activity, which prevents a sudden rise in postprandial blood glucose level by inhibiting α-amylase to slow down the breakdown of long-chain carbohydrates to glucose. It also controls the blood glucose level by inhibiting dipeptidyl peptidase IV (DPPIV), which prevents the rapid degradation of incretin and thus stimulates insulin secretion. Besides, it acts as an antioxidant agent to protect against lipid peroxidation and scavenge radicals. It showed antimicrobial properties by inhibiting the growth of pathogenic bacteria including Gram-positive Staphylococcus aureus and Bacillus subtilis, and Gram-negative Escherichia coli and Klebsiella pneumonia, and fungi which are Aspergillus niger, Penicillium digitatum and Colletotrichum gloeosporiodes. Furthermore, it exhibited antiulcerogenic effect by preventing gastric lesions and anti- inflammatory properties which interrupt the inflammation process by controlling cytokines secretion in macrophage lipopolysaccharide-stimulated cells. Therefore, A. occidentale may potentially be contributed to the treatment of various diseases, but continuous study is needed to determine further the bioactive compounds that are responsible for the mechanism of action.